2022
DOI: 10.1039/d1fo03952k
|View full text |Cite
|
Sign up to set email alerts
|

N-Acetylcysteine alleviates high fat diet-induced hepatic steatosis and liver injuryviaregulating the intestinal microecology in mice

Abstract: N-acetylcysteine (NAC), a well-accepted antioxidant, has been shown to protect against high fat diet (HFD)-induced obesity-associated non-alcoholic fatty liver disease (NAFLD) in mice. However, the underlying mechanism(s) of the beneficial...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 56 publications
1
20
0
Order By: Relevance
“…The increased activities of plasma aspartate transaminase (AST) and alanine aminotransferase (ALT) are gold indicators of liver injury. 22 In this study, we found that chronic alcohol feeding increased the activities of plasma ALT and AST, and the above indicators were the most increased in the AF/OO group (Fig. 2a and b).…”
Section: Resultssupporting
confidence: 52%
“…The increased activities of plasma aspartate transaminase (AST) and alanine aminotransferase (ALT) are gold indicators of liver injury. 22 In this study, we found that chronic alcohol feeding increased the activities of plasma ALT and AST, and the above indicators were the most increased in the AF/OO group (Fig. 2a and b).…”
Section: Resultssupporting
confidence: 52%
“…NAFLD, if not treated properly, can progress into a fatal disease, such as nonalcoholic steatohepatitis, fibrosis, cirrhosis, or liver cancer, which are the final stages of liver disease . According to one study, giving mice a high-fat diet (HFD) can cause NAFLD and liver damage, however, various studies indicate that natural products extracted from certain plants or fruits have protective effects against NAFLD. , In this study, the HFD-induced mouse model was studied to investigate the involvement and mechanism of astaxanthin (AT) in NAFLD.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, comprehensive examination of the NAFLD etiology induced by overnutrition and obesity showed that an alteration of the gut microbiota has emerged as a crucial element in promoting the occurrence of NAFLD ( 6 ). The levels of alanine aminotransferase (ALT), aspartate aminotransferase (AST), and triglycerides (TG) were significantly elevated by a high-fat diet (HFD) in C57BL/6 mice with NAFLD ( 26 ). Consequently, HFD decreased the special operational taxonomic units (OTUs) and Shannon diversity index of the microbiota, which suggested that HFD caused an imbalance in the homeostasis of the gut microbial community.…”
Section: Link Of Microbiota To the Non-alcoholic Fatty Liver Disease ...mentioning
confidence: 99%
“…In addition, Erysipelotrichaceae positively regulated the expression of Cidea, CD36, Acnat2, Mogat1, and GPAT3. Previous studies have suggested that Cidea, CD36, and GPAT3 are involved in the lipid metabolism pathway that drives the occurrence of HS ( 26 ). Third, F. prausnitzii can also regulate genes related to other pathways, such as IRS-1/2, IL-6, SOCS3, LEPR, and steroid response element binding protein-α (SREBP-α), to prevent the development of NAFLD ( 40 ).…”
Section: Link Of Microbiota To the Non-alcoholic Fatty Liver Disease ...mentioning
confidence: 99%